2010
DOI: 10.1021/ja101563t
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Intramolecular Isotope Effect on Aliphatic Hydroxylation by Chromobacterium violaceum Phenylalanine Hydroxylase

Abstract: The non-heme iron enzyme phenylalanine hydroxylase from Chromobacterium violaceum has previously been shown to catalyze the hydroxylation of benzylic and aliphatic carbons in addition to the normal aromatic hydroxylation reaction. The intrinsic isotope effect for hydroxylation of 3-cyclochexylalanine by the enzyme was determined to gain insight into the reactivity of the iron center. With 3-[ 2 H 11 -cyclohexyl]-alanine as substrate, the isotope effect on the k cat value was 1, consistent with an additional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…However, CvPheH will also catalyze the hydroxylation of cyclohexylalanine. This aliphatic hydroxylation reaction does exhibit a large deuterium kinetic isotope effect (∼15) (19), and amino acid hydroxylation is reported to be fully coupled to tetrahydropterin oxidation for this substrate (33). Similar rapid-quench Mössbauer experiments were carried out with deuterated cyclohexylalanine in an attempt to increase the amount of the Fe(IV) intermediate, but the intermediate could not be detected with this substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, CvPheH will also catalyze the hydroxylation of cyclohexylalanine. This aliphatic hydroxylation reaction does exhibit a large deuterium kinetic isotope effect (∼15) (19), and amino acid hydroxylation is reported to be fully coupled to tetrahydropterin oxidation for this substrate (33). Similar rapid-quench Mössbauer experiments were carried out with deuterated cyclohexylalanine in an attempt to increase the amount of the Fe(IV) intermediate, but the intermediate could not be detected with this substrate.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of the bacterial PheH, the structure of the ferric enzyme shows a bidentate glutamate , in contrast to the eukaryotic enzymes. Still, the reactivities of the hydroxylating intermediates in the eukaryotic and prokaryotic enzymes appear to be essentially identical on the basis of their similar abilities to catalyze aromatic, benzylic, and aliphatic hydroxylation .…”
mentioning
confidence: 99%
“…Aromatic amino acid hydroxylases have been demonstrated to operate by a mechanism that involves an NIH shift. In all previous mechanistic studies (typically with Trp and Phe hydroxylases) the deuterium or tritium label from the hydroxylation position was present in >60 % of the product . Unexpectedly, in this work with Phe3H, the second deuterium atom was lost.…”
Section: Resultsmentioning
confidence: 53%
“…Isotopic labelling has been used extensively to study the catalytic mechanisms of aromatic amino acid hydroxylases . In this work, substrate deuterium labelling was employed to probe the mechanism of Phe3H .…”
Section: Resultsmentioning
confidence: 99%
“…With the intent to augment its accumulation, we used the perdeuterated cyclohexylalanine analog. Despite the fact that previous studies have shown that the reaction of Cv PheH with this analog results in hydroxylation of one of its aliphatic C-H bonds, exhibits a deuterium kinetic isotope effect of ∼15, and is fully coupled [75], the ferryl intermediate does not accumulate to a detectable level, as judged by the absence of the well-resolved high-energy line of the ferryl complex in the Mössbauer spectra, in the reaction of Cv PheH with the perdeuterated analog, presumably because addition of O 2 (and therefore formation of the intermediate) is significantly slowed by the diminished ST efficacy of the non-native substrate [73]. …”
Section: Introductionmentioning
confidence: 99%